Dependence of success in playing activity of volley-ballers from psychological climate in command. - Kazakov D.A (Kharkov National Pedagogical University, 2011)
The features of mutual relations are considered in the command of volley-ballers, the analysis of psychological climate is carried out in a womanish command. In an experiment two commands of volley-ballers took part for 18 sportswomen by age of 19-23. All of them on qualification have the first sporting digit. It is set that in a successful command the friendly and altruism types of relations prevail between the members of command. In a command with low progress in sporting activity dominant are aggressive and selfish types of relations. Dependence of sporting results is well-proven on a psychological climate in a command.